Choice Between Salary and Employer Brand: The Roles of Materialism and Inclination to Develop an Identity-Motives-Based Relationship With an Employer Brand - Styśko-Kunkowska, Małgorzata A.; Kwinta, Zuzanna (Frontiers in Psychology, 2020)
Despite recent interest in individual differences in psychological meanings of consumer brands, the concept of psychological employer brand as a factor independent of particular brands has not been examined. Drawing on an instrumental-symbolic framework, person–organization fit literature, and theory and research on salary and materialism, and combining consumer brand approaches with motivated identity construction theory, we examine the role of materialism and identity-motives-based inclination for the self–employer brand relationship in the situation of a dilemma between two job offers: one proposed by a strong employer brand with an unattractive salary and one from a subjectively weak brand with an attractive salary. A homogenous sample of 101 university students in academic fields related to financial careers participated in a quasi-experimental study. We found that participants preferred the offer from the weak employer brand with an attractive salary compared to the strong employer brand with an unattractive salary; however, supporting our hypothesis, those who preferred this offer anticipated lower job satisfaction. Following expectations, materialism negatively and inclination for self–employer brand relationship positively predicted preferences and evaluations of the unattractive salary offer proposed by the strong employer brand. However, materialism negatively predicted anticipated job satisfaction regarding this offer, as well as positively predicting evaluation of the weak brand with attractive salary job offer. Despite all the detailed hypotheses not being supported, the findings confirm the role of materialism in job offer preference and introduce the inclination to develop an identity-motives-based relationship with an employer brand as an important factor in reactions toward different employer branding recruitment strategies. We discuss the results in light of previous theories and research on person–organization fit, materialism, and brand effects, and consider potential short- and long-term outcomes of recruitment strategies.